Pendekatan Politik dalam Ibadah Zakat: Political Approach in Obligatory Charity (Zakat): The Role of the State in Zakat Management from a Classical Islamic Perspective to Contemporary Indonesia - Juraidi, Ahmad; Husnah, Sitti Nur Sapiah; Saepulloh, Maman (Direktorat Jenderal Bimbingan Masyarakat Islam, 2025)
Zakat is one of the fundamental pillars of Islam that plays a vital role in shaping a just and prosperous society. Beyond its spiritual significance, zakat serves as a socio-economic mechanism aimed at eradicating poverty and reducing inequality. Historically, zakat has been systematically managed under state authority, beginning from the time of Prophet Muhammad (peace be upon him) and the Khulafa al-Rashidun. This study explores zakat from a political approach by examining its relationship with Islamic governance and state policy. Using a descriptive-qualitative method and literature review, this paper analyzes classical and contemporary Islamic sources to understand how zakat functions within a political framework. The findings suggest that zakat is not only a personal religious obligation but also has the potential to serve as a public policy instrument when institutionalized by the state. A political approach to zakat highlights that Islam does not separate moral values from governance; instead, it offers a comprehensive system that integrates ethical wealth distribution with state responsibility. Therefore, linking zakat with political authority is crucial for realizing the objectives of Sharia in addressing modern socio-economic challenges. Through such integration, zakat can contribute significantly to the development of a more equitable, ethical, and welfare-oriented society.